Metagenomic Applications in the Diagnosis of Reproductive Disorders in Ruminants: Subject Review - ZinAlabidin, Mohammed M; ZinAlabidin, Mohammed M; Tawfeeq, Mustafa Muwafaq; Baker, Ahmed Gh. (American Journal of Biodiversity, 2025)
This study demonstrates that the application of metagenomics to the investigation of reproductive disorders in cattle, sheep and goats improves the sensitivity of pathogen detection by approximately 40 % compared with traditional culture and single-target PCR methods. In addition, metagenomic profiling uncovers disorder-specific microbial signatures: Bacteroides–Fusobacterium–Trueperella predominate in postpartum metritis/endometritis, and Enterococcus/Mycoplasma in repeat-breeder syndrome, while high Prevotella load is associated with sperm DNA fragmentation and male subfertility. A working diagnostic cut-off for pathological dysbiosis, =/> 10 % dominance of a specific pathogenic genus combined with a Shannon diversity index < 2, was suggested. The standardized workflow recommended here (i.e., immediate −80 °C sample freezing, DNA extraction, library prep, and sequencing) can result in a clinically actionable report in 24 h and a per-sample cost ≈ US 25 with batch processing. Remaining challenges include laboratory/reagent contamination risk, equivocal ruminant-specific reference databases, international interpretive standards for reporting, and greater cost compared to multiplex qPCR methods. However, handheld Nanopore devices for on-field analysis within < 30 min, integration of metagenomics with transcriptomics, high-resolution machine-learning models, region-specific microbiome atlases, and microbe-targeted interventions (probiotics, phage therapy) collectively signal a shift from reactive to preventive and predictive fertility management—supporting sustainable meat and milk production by lowering dependence on broad-spectrum antibiotics.